Retrospective evaluation of the agreement between thoracic point-of-care ultrasound and thoracic radiographs in cats with recent trauma: 111 cats - Vidal, Pierre-André; Boysen, Søren R.; Fordellone, Julie; Nectoux, Alexandra; Allaouchiche, Bernard; Pouzot-Nevoret, Céline (Frontiers in Veterinary Science, 2024)
Introduction: Motor vehicular trauma, bite wounds, high-rise syndrome, and trauma of unknown origin are common reasons cats present to the emergency service. In small animals, thoracic injuries are often associated with trauma. The objective of this retrospective study was to evaluate limits of agreement (LOA) between thoracic point‐of‐care ultrasound (thoracic POCUS) and thoracic radiography (TXR), and to correlate thoracic POCUS findings to animal trauma triage (ATT) scores and subscores in a population of cats suffering from recent trauma. Methods: Cats that had thoracic POCUS and TXR performed within 24 hours of admission for suspected/witnessed trauma were retrospectively included. Thoracic POCUS and TXR findings were assessed as "positive" or "negative" based on the presence or absence of injuries. Cats positive on thoracic POCUS and TXR were assigned 1 to 5 tentative diagnoses: pulmonary contusions/hemorrhage, pneumothorax, pleural effusion, pericardial effusion, and diaphragmatic hernia. When available ATT scores were calculated. To express LOA between the two imaging modalities a kappa coefficient and 95% CI were calculated. Interpretation of kappa was based on Cohen values. Results: One hundred and eleven cats were included. 83/111 (74.4%) cats were assessed as positive based on thoracic POCUS and/or TXR. Pulmonary contusion was the most frequent diagnosis. The LOA between thoracic POCUS and TXR were moderate for all combined injuries, moderate for pulmonary contusions/hemorrhage, pneumothorax, diaphragmatic hernia, and fair for pleural effusion. Cats with positive thoracic POCUS had significantly higher median ATT scores and respiratory subscores compared to negative thoracic POCUS cats. Discussion: The frequency of detecting intrathoracic lesions in cats was similar between thoracic POCUS and TXR with fair to moderate LOA, suggesting thoracic POCUS is useful in cats suffering from trauma. Thoracic POCUS may be more beneficial in cats with higher ATT scores, particularly the respiratory score.